A Study on Non-Performing Assets (NPA) of Selected Private Sector Banks in India - Priyanka Meghanathi; Seema M. Dodiya (Celebes Scholar pg, 2021)
The banking industry is critical to the success of any economy since it satisfies societal requirements. A bank is a financial entity that provides its clients with a variety of banking and other financial services. India's banking industry has been grappling with mounting non-performing assets. The rise of Non-Performing Assets has a significant impact on a bank's profitability. This research was undertaken in order to analyze the non-performing assets of a sample of chosen private sector banks in India. For that purpose, the researcher chose the top four private sector banks, namely HDFC bank, ICICI bank, Axis bank, and Indusland bank, based on their net sales from 2016-17 to 2020-21. To analyze non-performing assets in a selected private sector in India, gross non-performing assets (NPAs), net non-performing assets (NPAs), and net profit ratios were chosen. To test the hypothesis, the researcher employed a one-way ANOVA with a significance level of 5%. The study's primary conclusions include that HDFC bank's average GNPA and average NNPA are the lowest in the industry, while ICICI banks are the highest.